International Students Experiences and Identity Development while Joining Study in Indonesia: Narrative Inquiry in Magister Study Level - Mustagis, R. Muhammad Satria Gyas; Sukarno, Sukarno (Journal of Languages and Language Teaching, 2024)
International students choose Indonesia as a destination for their studies for various reasons, and they face unique challenges while studying abroad in the country. The purpose of this study is to explore the experiences of master's students who participate in study abroad programs in Indonesia. By understanding these experiences, the study aims to provide insights that can enhance the support and structure of such programs. To achieve this, the researchers employed a narrative inquiry methodology, focusing on the stories of two international participants in the program. This approach allows for an in-depth understanding of the participants' personal experiences and the meaning they derive from them. Through the analysis of their narratives, the study highlights the value of studying overseas for a student’s overall development. The findings emphasize that studying abroad in Indonesia offers significant benefits, contributing to the students' personal and academic growth. The experiences shared by the participants reveal how they navigated the cultural, social, and academic challenges encountered during their time in Indonesia. These challenges, while initially daunting, ultimately contributed to their resilience and adaptability. In conclusion, the study underscores the importance of international study programs in fostering global understanding and cooperation. By sharing the narratives of the international participants, the research highlights both the challenges and the profound benefits of studying abroad. These insights are crucial for universities aiming to provide enriching and supportive study abroad experiences that contribute to the personal and professional development of their students.